(untitled) (Research, Society and Development, 2021)
The goal of this article is to present the investigation that resulted in a theoretical-methodological path to research genesis and development processes of social representations. The research was guided by the Social Representations Theory (SRT) assumptions. The qualitative research had SRT data from books and scientific articles. We sought the contributions of Textual Discursive Analysis to evaluate the findings on SRT. Six elements were considered essential when designing an investigation on the genesis, contribution and resignification of a Social Representation (SR), namely: (1) identification of the SR object; (2) initial characterization of the profile of the investigated group, (3) understanding the interlocutors’ daily lives, (4) identification of Social Representations about the object of SR, (5) information processing steps: objectification and anchoring; (6) relations between SR and social practices. The theoretical-methodological alternative outlined may contribute to similar research provided adjustments to the particular social interaction context of the group participants.